2010
DOI: 10.1109/tns.2010.2047731
|View full text |Cite
|
Sign up to set email alerts
|

Regularized Fully 5D Reconstruction of Cardiac Gated Dynamic SPECT Images

Abstract: In our recent work, we proposed an image reconstruction procedure aimed to unify gated imaging and dynamic imaging in nuclear cardiac imaging. With this procedure the goal is to obtain an image sequence from a single acquisition which shows simultaneously both cardiac motion and tracer distribution change over the course of imaging. In this work, we further develop and demonstrate this procedure for fully 5D (3D space plus time plus gate) reconstruction in gated, dynamic cardiac SPECT imaging, where the challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…Then Segars et al (2013) extended the XCAT beyond these reference anatomies to a library of 35 male and 23 female 4D computational phantoms by developing a series of anatomically variable 4D XCAT adult phantoms for imaging research. The NCAT and XCAT phantoms have been used by other research groups to simulate radiation dose from radiography (Tabary et al 2009, Niu et al 2010) and radiotherapy (McGurk et al 2010). A research group constructed a version of the XCAT heart to enhance the range of cardiac disorders that can be studied using the phantom (Veress et al 2011).…”
Section: The Evolution Of Computational Phantomsmentioning
confidence: 99%
“…Then Segars et al (2013) extended the XCAT beyond these reference anatomies to a library of 35 male and 23 female 4D computational phantoms by developing a series of anatomically variable 4D XCAT adult phantoms for imaging research. The NCAT and XCAT phantoms have been used by other research groups to simulate radiation dose from radiography (Tabary et al 2009, Niu et al 2010) and radiotherapy (McGurk et al 2010). A research group constructed a version of the XCAT heart to enhance the range of cardiac disorders that can be studied using the phantom (Veress et al 2011).…”
Section: The Evolution Of Computational Phantomsmentioning
confidence: 99%
“…Segars ran simulations of PET, SPECT, and CT to demonstrate the applicability of the phantoms. The NCAT and XCAT phantoms have been used by several research groups to simulate radiation dose from radiography [104,105] and radiotherapy [237,106]. A research group constructed a version of the XCAT heart to enhance the range of cardiac disorders that can be studied using the phantom [107].…”
Section: Brep Phantoms From 2000s To Presentmentioning
confidence: 99%
“…In (5), l k M denotes the motion-compensated prediction operator from gate l to gate k, C is normalization constant. As mentioned in the introduction, the prior form in (4) and (5) was applied in our earlier work for 5D dynamic image reconstruction [3], and is adapted for direct kinetic reconstruction in this work.…”
Section: Maximum a Posterior Reconstructionmentioning
confidence: 99%
“…In our recent work [3][4], we have been investigating the feasibility of reconstructing cardiac gated dynamic images (termed 5D imaging, consisting of 3D space plus gate plus time) from a single acquisition, of which the goal is to provide information about both tracer kinetics and cardiac motion. We have demonstrated that despite the great challenges it is indeed feasible to obtain such a 5D image sequence, and that, more importantly, the kinetic information derived from the reconstructed dynamic images can be effective for discriminating normal from perfusion defects [5].…”
Section: Introductionmentioning
confidence: 99%